An Accelerator Mass Spectrometry‐Enabled Microtracer Study to Evaluate the First‐Pass Effect on the Absorption of YH4808. Issue 3 (26th May 2017) - Kim, A; Yu, B‐Y; Dueker, SR; Shin, K‐H; Kim, HS; Ahn, H; Cho, J‐Y; Yu, K‐S; Jang, I‐J; Lee, H
Abstract : 14 C‐labeled YH4808, a novel potassium‐competitive acid blocker, was intravenously administered as a microtracer at 80 μg (11.8 kBq or 320 nCi) concomitantly with the nonradiolabeled oral drug at 200 mg to determine the absolute bioavailability and to assess the effect of pharmacogenomics on the oral absorption of YH4808. The absolute bioavailability was low and highly variable (mean, 10.1%; range, 2.3–19.3%), and M3 and M8, active metabolites of YH4808, were formed 22.6‐ and 38.5‐fold higher after oral administration than intravenous administration, respectively. The product of the fraction of an oral YH4808 dose entering the gut wall and the fraction of YH4808 passing on to the portal circulation was larger in subjects carrying the variants of the CHST3, SLC15A1, and SULT1B1 genes. A combined LC+AMS is a useful tool to construct a rich and highly informative pharmacokinetic knowledge core in early clinical drug development at a reasonable cost.